Diseño Y Construcción De Una Máquina De Desgaste Abrasivo A Tres Cuerpos Según Norma Astm G65 (2023)
In this project, a machine for abrasive wear testing was built and designed in accordance with the ASTM G-65 standard, the design was carried out with the SolidWorks program, which consists of a sealed cabin, a material extraction control system particulate with a cyclone type collector filter, whose function is to collect the dust at the end of the test. The machine has an electrical control board, programmed with the parameters specified according to the ASTM G65 standard (revolutions, time and type of test), and in this way it is guaranteed to carry out the three-body abrasive wear test safety and practically.